A rapid algorithm for millimeter-wave near-field three-dimensional image reconstruction based on FiNUFFT - Letian Zeng; Sheng Zhang; Yuanyuan Huai; Qi Mao; Jingzhao Li; Zhaohui Luo; Yunhuai Zou (EURASIP Journal on Advances in Signal Processing)
Abstract The data to be processed in near-field three-dimensional (3D) imaging is of a considerable volume. The interpolation operation is both time-consuming and introduces interpolation errors, which considerably degrade both accuracy of the imaging and the efficiency of the computing. In order to address these challenges, this paper presents a rapid algorithm for millimeter-wave near-field 3D image reconstruction based on the Flatiron Institute nonuniform fast Fourier transform (FiNUFFT). The presented algorithm replaces the traditional Stolt interpolation method and the subsequent inverse fast Fourier transform (IFFT) in the corresponding dimension with FiNUFFT. This results in a notable reduction in the computational burden, a decrease in processing time, and the circumvention of the interpolation error introduced by the Stolt interpolation. The proposed algorithm is designed to ensure the reconstruction of high-quality 3D images, with the potential to significantly enhance the efficiency of computation. This provides a more efficient and accurate solution for millimeter-wave near-field 3D imaging. The effectiveness of the proposed algorithm has been validated through simulations and real data experiments.